Athletic identity, values and self-regulatory efficacy governing hypercompetitive attitudes. (January 2022) - Albouza, Youssef; Chazaud, Pierre; Wach, Monique
Abstract: This study adaptes the identity-value model (IVM) of self-regulation to examine a structural model of the psychosocial processes governing hypercompetitive attitudes among athletes. Structural equation modeling of data from 522 competitors, aged 11–23 years, showed that the effect of athletic identity on hypercompetitive attitudes was serially mediated via athletes' values and self-regulatory efficacy. Athletic identity positively predicted all athletes' values for morality, competence, and status. Moral values (positively) and status values (negatively) predicted self-regulatory efficacy, which in turn negatively predicted hypercompetitive attitudes. Self-regulatory efficacy (fully) mediated the negative effect of moral values and (partially) mediated the positive effect of status values on hypercompetitive attitudes. Also, these effects were invariant across gender, sports types, and age. This study extends the application of the IVM, the athletic identity maintenance model (AIMM), and the Schwartz' basic values theory, by suggesting that athletic identity is a strong predicator of athletes' values and can operate in concert with athletes' values and self-regulation efficacy in governing hypercompetitive attitudes. Highlights: Athletic identity positively contributed to predict the hypercompetitive attitudes. Athletic identity indirectly predicted hypercompetitive attitudes through athletes' values and self-regulatory efficacy. Athletic identity indirectly predicted self-regulatory efficacy through athletes' values. Self-regulation efficacy governed the impact of athletes' values on hypercompetitive attitudes. Status values enhanced predictive strength of athletic identity on hypercompetitive attitudes.